PENGARUH VISKOSITAS MINYAK PELUMAS TERHADAP KONSUMSI BAHAN BAKAR - Afvin Ismaya Tanumurti; Basmal; Muhamad Amiruddin, M.Pd. (Journal of Automotive Technology Vocational Education, 2025)
Rapid technological advances in the automotive field have led to improvements in vehicle engine performance and efficiency. One crucial factor that supports engine performance is the lubrication system. The right viscosity value will help the lubrication process run optimally, reduce friction between components, and prevent premature damage to the engine. Fuel efficiency in motorcycles is a major concern for users because it is directly related to daily expenses. The purpose of this study is to determine the effect of lubricant viscosity on fuel consumption in the Mio Sporty. The methods used are literature study, observation, experimentation or testing, and documentation. After conducting several experiments using lubricants with different viscosities, it was found that the higher the viscosity, the more fuel was consumed. This is due to greater internal engine friction, which requires more power to maintain rotation, thereby impacting fuel efficiency. The conclusion is that the higher the oil viscosity, the greater the fuel consumption.   Keywords: oil viscosity, fuel consumption.